Game-based application for normalization learning / Nik Nuru Izzasalwani Nik Pa, Norfiza Ibrahim and Azmi Abu Seman - Nik Pa, Nik Nuru Izzasalwani; Ibrahim, Norfiza; Abu Seman, Azmi (UiTM Cawangan Perlis, 2017)
Normalization is a relational database design for the organizing data process to minimize redundancy. The main aim for this study is to develop a game application for normalization learning. Besides, the study also focusing on identifying the preferred learning technique for normalization, the suitable multimedia and game-based elements for the development of a game application for normalization learning, and measuring the applicability of the application. Design science research methodology was implemented throughout the study which consists of five phases. Unity 3D software is used to develop a game-based application for normalization learning. The application has applied the Multimedia Principles, Game Based Principles and Marczewski's Gamification Framework in the development. Game-based environment provides an alternative on how to learn database normalization interactively. There are two types of testing used in measuring the application; heuristic evaluation and user acceptance at public university and were analyzed based on statistical analysis. The analysis from heuristic evaluation indicates that the game-based application is usable and practicable for normalization learning while analysis by user acceptance shows that the respondents are strongly agrees on the technical aspects in the application and they are ready to use this application. Therefore, the research has achieved its objective. Besides, the application will enhance the student’s ability to easily recognize the various normal forms and will be skillful in the hands-on process of database normalization.